2014
DOI: 10.1590/s0103-84782014000300012
|View full text |Cite
|
Sign up to set email alerts
|

Morfogênese da grama-tapete em resposta à adubação com dejeto líquido de suínos

Abstract: RESUMO Este trabalho teve como objetivo avaliar a morfogênese da grama-tapete (Axonopus affi nis) adubada durante dois anos com dejeto líquido de suínos (DLS). Na média de dois anos, foram aplicados 0, 51, 102, 153, 204 ABSTRACT This study aimed to evaluate the morphogenesis of carpet grass fertilized for two years with pig slurry (PS). On the average of two years were applied 0, 51, 102, 153, 204 , respectively. The morphogenesis was evaluated in the spring and summer of 2008-2009 and 2009-2010 ) and phyll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…It is still little cultivated in Brazil for ornamental purposes; however, it shows expansion potential for its decorative effect, hardiness and resistance to trampling and cold. Travi et al (2014) reported that A. affinis is one of the most important grass species in native pastures of Southern Brazil, besides being aggressive and resistant to trampling and cold.…”
Section: Introductionmentioning
confidence: 99%
“…It is still little cultivated in Brazil for ornamental purposes; however, it shows expansion potential for its decorative effect, hardiness and resistance to trampling and cold. Travi et al (2014) reported that A. affinis is one of the most important grass species in native pastures of Southern Brazil, besides being aggressive and resistant to trampling and cold.…”
Section: Introductionmentioning
confidence: 99%